An??lise do custo-efetividade de materiais odontol??gicos utilizados na t??cnica de Tratamento Restaurador Atraum??tico (ART) em sa??de p??blica - Sobral, Ana Paula Taboada (2016)
Limited resources have been proposed for Oral Health in Brazil, causing most of the population to go without access to new materials and technologies that optimize dental treatments. This scenario underscores the need for studies with economic analyses that assess the cost effectiveness of materials used in dental procedures within Public Health. The general goal of this paper is to therefore assess two commercial brands of glass ionomer cements proposed for ART (Atraumatic Restorative Treatment) and to see which product is most cost effective for Basic Dental Care. To achieve the aim proposed for this study, a quantitative approach was used, of an exploratory, experimental and cost-effectiveness nature. Methodological procedures were carried out in two stages. The first stage consisted of a clinical study of the effectiveness of two glass ionomer cements (G1- ION Z??-FGM and G2 - Ketac Molar Easymix??- 3M Espe) used for the ART technique on deciduous teeth, simulating the care conditions in Basic Oral Healthcare. In the second phase, a cost-effectiveness study was done of the same materials, where the results of the clinical phase were used to find that there was no statistical significant difference (p>0,05) in effectiveness between the two groups (G1 and G2) in the period of 3, 6 and 12 months and that the ION Z??-FGM (G1) material was R$ 18.84 more affordable/cheaper than the Ketac Molar Easymix??- 3M Espe (G2) product, which is equally effective. So in conclusion, ION Z??-FGM (G1) proved to be the most cost effective material for Basic Dental Care.